European Union anti-piracy initiatives in the Horn of Africa: linking land-based counter-piracy with maritime security and regional development. Issue 9 (2nd September 2017) - Winn, Neil; Lewis, Alexandra
Abstract: Piracy off the coast of Somalia has resulted in a steady decline in trade through the Arabian Sea and higher costs of doing business for multiple world regions. The EU has responded to the threat with a large-scale anti-piracy operation in the Horn of Africa, which constitutes the first free-standing Common Security and Defence Policy (CSDP) military operation that is not entirely dependent on North Atlantic Treaty Organization (NATO) planning and assets. The operation is designed to interdict Somali piracy operations across the Gulf of Aden and to keep some of the world's busiest sea lanes open for reasons of world trade. This article argues that the EU preoccupation with military solutions to the piracy problem, based on interventions through the Somali federal government with an emphasis on security, is insufficient because it fails to address the underlying causes of piracy and misunderstands the Somali socio-cultural-security nexus and the need for practical longer term land-based approaches to development. The reduction of Somali piracy activities can be linked to this increased military response capacity as well as to increased security precautions undertaken by shipping companies, but none of these strategies has succeeded in dismantling piracy networks. They therefore offer only a temporary and costly stopgap measure.